Studi Fenomenologi tentang Pengalaman Mahasiswa Universitas Medan Area dalam Menggunakan Aplikasi Whatsapp sebagai Media Komunikasi Akademik dan Sosial - Tobi Ardian Tarigan; Syafrizaldi Syafrizaldi (Mahesa Research Center, 2025)
This study aims to explore the experiences of Universitas Medan Area students in using WhatsApp as a medium for academic and social communication. A qualitative approach with a phenomenological method was used to understand students subjective experiences. Data were collected through in-depth interviews and observations of communication activities within academic WhatsApp groups. The findings indicate that (1) WhatsApp facilitates students in accessing academic information, discussing with lecturers, and coordinating coursework, although challenges such as information overload and text-based miscommunication persist; (2) the application supports academic collaboration through document sharing and group discussions, but low engagement from members can hinder productivity; (3) besides academic communication, WhatsApp strengthens students social networks but can also become a source of distraction and social pressure; (4) students adopt strategies such as notification management and integrating additional academic platforms to enhance productivity, while institutional policies also play a role in fostering more effective academic communication. This study concludes that while WhatsApp plays a crucial role in academic and social communication, its optimization highly depends on individual strategies and institutional policies.